The Development of Message-Design Model in Blended Learning - Rahmi, Ulfia; Effendi, Z. Mawardi; Ansyar, Mohd; Jasrial, Jasrial (The Asian Journal of Technology Management (AJTM), 2017)
Abstract. The researcher found a problem in designing an instruction often ignore the message design because it is focused on syntax and learning systems, including the design of innovative learning such as e-learning, online learning, blended learning and mobile learning. Based on these problems, the researcher develops a model of design message in blended learning. The goal is to help the educators to facilitate learners to interpret and construct teaching materials. The development used ADDIE models. Qualitative and quantitative data were collected through observation, interviews, questionnaires, and tests in order to produce a model of message design. The validity of this products was tested by expert and the practicality and effectivity testing by the user in the course of Theory of Learning and instruction. The result of this development consists of (1) the book of model design messages in blended learning, and (2) the learning tool that consists of teaching materials, media presentations, e-learning, syllabus, SAP that is valid, practical and effective. The Book model can be used by designers of instruction, learning consultant, and lecturer/educator in helping learners to interpret and construct learning message so that they have an ability to generalize the learning and become independent learners.Keyword: Â Blended learning, online learning, message design, learning theory, ADDIE model